Morphologica evaluation of Ananas comosus var. erectifolius (L. B. Smith) Coppens & F. Leal-Bromeliacea (Research, Society and Development, 2021)
The objective of this work was to determine morphological descriptors of accessions of Curauá through morphological characters aiming at the evaluation of germplasms, at Embrapa Amazônia Oriental, in Belém, PA. Seven quantitative morphological characters of 42 accessions of Curauá were studied, totaling 210 individuals, conserved in I live in the Medicinal Plants Garden. The data were submitted to multivariate analyzes, direct selection and selection with reanalysis were carried out grouped in two methods and based on the average Euclidean distance used in the formation of the clusters by the methods Unweighted Paired Group Method Using ArithmeticAverages -UPGMA for Tocher's optimization and for analysis of main components. Of the characters evaluated, none were shown to be reduntant, so there were no discards. Based on the average Euclidean distance, they presented three shortest distances 0.052; 0.084 and 0.085 between pairs of accessions and allowed to separate them into three divergent groups by the UPGMA method and by the Tocher method there was the formation of four divergent groups. The accessions of Ananas comosus var.erectifolius have morphological variability according to the seven quantitative characters under study, with the characters leaf length, plant height and number of leaves being the main contributors to the divergence between the accessions.